Rethinking hierarchy : we need to reconceive managerial authority for today's business environment, not eliminate it - Foss, Nicolai J., 1964-; Klein, Peter G. (MIT Sloan Management Review, 2023)
For all the hype around bossless companies, managerial authority and hierarchy are still the best ways to ensure coordination, cooperation, creativity, predictability, and accountability in large organizations. But authority and hierarchy must be aligned to a company’s specific needs. To fine-tune them, leaders should consider the need for speed in decision-making, the extent of employee knowledge, what knowledge is truly required, employee feelings of ownership, and procedural justice.